2014
DOI: 10.1242/jeb.102855
|View full text |Cite
|
Sign up to set email alerts
|

Ambient noise causes independent changes in distinct spectro-temporal features of echolocation calls in horseshoe bats

Abstract: One of the most efficient mechanisms to optimize signal-to-noise ratios is the Lombard effect -an involuntary rise in call amplitude due to ambient noise. It is often accompanied by changes in the spectrotemporal composition of calls. We examined the effects of broadband-filtered noise on the spectro-temporal composition of horseshoe bat echolocation calls, which consist of a constantfrequency component and initial and terminal frequency-modulated components. We found that the frequency-modulated components be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 11 publications
0
11
0
Order By: Relevance
“…Previous research has demonstrated that spectral shifts in human speech are dependent on the spectral content of the noise [ 6 ]. However, recent data from noise exposure experiments with avian and mammalian taxa show that some vertebrate species are capable of immediate and independent changes to the amplitude and spectral characteristics of vocalizations during increased noise [ 16 18 ], suggesting that spectral modifications may serve a communicative function during increased noise. This view accords with the recent suggestion that multiple levels of vocal control may be active during Lombard vocalizations.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has demonstrated that spectral shifts in human speech are dependent on the spectral content of the noise [ 6 ]. However, recent data from noise exposure experiments with avian and mammalian taxa show that some vertebrate species are capable of immediate and independent changes to the amplitude and spectral characteristics of vocalizations during increased noise [ 16 18 ], suggesting that spectral modifications may serve a communicative function during increased noise. This view accords with the recent suggestion that multiple levels of vocal control may be active during Lombard vocalizations.…”
Section: Introductionmentioning
confidence: 99%
“…The FM component in horseshoe bat echolocation pulses functions in determining target distance [ 42 , 64 , 65 ]. The spectral and temporal features of the FM component have been shown to vary depending on a number of external factors, including the level of ambient noise [ 66 ] as well as the presence of other bats, both con- and heterospecifics [ 67 ]. The spectral features of the CF component are restricted by the acoustic fovea, limiting their ability to be adjusted to facilitate communication (but see [ 63 , 67 , 68 ]).…”
Section: Discussionmentioning
confidence: 99%
“…Independent adjustments of signal amplitude and spectral parameters have also been documented in a horseshoe bat species (Hage et al, 2013(Hage et al, , 2014. Independent control of different signal parameters might be a crucial feature for echolocating bats, which deal with moving prey and/or acoustically challenging environments in the dark.…”
Section: Biomechanical Link Underlying Signal Plasticitymentioning
confidence: 96%